Altered Spontaneous Brain Activity in Patients With Diabetic Osteoporosis Using Regional Homogeneity: A Resting-State Functional Magnetic Resonance Imaging Study - Liu, Min; Li, Jiang; Li, Juan; Yang, Hui; Yao, Qianqian; Zheng, Xiuzhu; Zhang, Zheng; Qin, Jian (Frontiers in Aging Neuroscience, 2022)
Background:The pathophysiological mechanism of cognitive impairment by osteoporosis in type 2 diabetes mellitus(T2DM) remains unclear.The aim of this study was to investigate the regional spontaneous brain activity changes of diabetic osteoporosis(DOP) patients, and the correlation between abnormal brain regions and bone metabolites furtherly. Methods:A total of twenty-nine subjects with T2DM were recruited, including fourteen patients with DOP and thirteen non-osteoporosis patients(controls,CON). Based on the resting-state functional magnetic resonance imaging(rs-fMRI) datasets acquired from all the subjects,a two-sample t-test was performed on individual normalized regional homogeneity (ReHo) maps. Spearman correlation analysis was performed between the abnormal ReHo regions with the clinical parameters and Montreal Cognitive Assessment(MOCA) scores. Results:In the DOP group, we demonstrated significantly increased ReHo values in the left middle temporal gyrus(MTG), right superior occipital gyrus(SOG), right superior parietal lobule(SPL),right angular gyrus(AG) and left precuneus(PE). Additionally, We also found a significant positive correlation between increased ReHo values in the left MTG and the average bone mineral density(BMD AVG), averge T scores(T AVG). The ReHo values of the right SOG and right SPL showed negative correlation with MOCA scores, as well as negative correlation between increased ReHo values in the right SPL and osteocalcin(OC) level. Conlusion: DOP patients showed increased spontaneous activity in multiple brain regions.The results indicate that osteoporosis exacerbates cognitive impairment and brain damage. And the OC might be considered as a bone marker to track the progression of cognitive impairment.